Comparison of the Aedes spp Eggs Number Trapped in Ovitrap Using Rainwater and Municipal Water - Rinaldi Daswito; Ronaldo Ronaldo; Risman Kurnia; Alkausyari Aziz (JURNAL PROTEKSI KESEHATAN, 2022)
Dengue Hemorrhagic Fever (DHF) is still a public health problem in Indonesia. The number of sufferers and the area of their distribution is increasing along with the increasing mobility and population density. The purpose of this study was to compare the number of eggs trapped in the ovitrap using rainwater and PDAM water. This type of research was a quasi-experimental design with a post-test-only design. Determination of the sampling location was done by determining the point of the house of DHF sufferers and their surroundings. The total number of eggs trapped in the ovitrap was 3829 eggs. The number of rainwater ovitraps (2279) traps more Aedes spp mosquito eggs than PDAM water ovitraps (1553). Ovitrap index of 61% in this study was included in the level 4 category or high above 40%. The results of the Mann-Whitney analysis with p-value = 0.637 > 0.05 means that it did not showed a significant difference between the number of eggs trapped in the rainwater ovitrap and PDAM water. There was no difference in the average number of eggs in rainwater and PDAM water ovitrap media. The community of RT 2 and RT 3 RW 1 are expected to always carry out the Mosquito Nest Eradication (PSN) movement at least once a week to reduce the proliferation of the DHF vector.